Sustainability in Logistics and Supply Chain Management: New Designs and Strategies - Wolfgang Kersten; Thorsten Blecker; Christian M. Ringle (epubli GmbH, 2015)
The HICL-Conference celebrates its 10th anniversary, indicating major interest in the research fields of supply chain management and logistics. They are dedicated to make recommendations for new approaches and solutions that enable companies to cope with current and future challenges in supply chains and logistics. The second volume of the 2015 conference provides valuable insights into the highly relevant topic of sustainability in logistics and supply chains. Contributions concern achievement of sustainability and application of sustainability concepts in various supply chains.
urn:nbn:de:gbv:830-88213433; https://econpapers.repec.org/RePEc:zbw:hiclch:209270; https://econpapers.repec.org/RePEc:zbw:hiclch:209271; https://econpapers.repec.org/RePEc:zbw:hiclch:209272; https://econpapers.repec.org/RePEc:zbw:hiclch:209273; https://econpapers.repec.org/RePEc:zbw:hiclch:209274; https://econpapers.repec.org/RePEc:zbw:hiclch:209275; https://econpapers.repec.org/RePEc:zbw:hiclch:209276; https://econpapers.repec.org/RePEc:zbw:hiclch:209277; https://econpapers.repec.org/RePEc:zbw:hiclch:209278
Keywords: 650; Logistics; Supply Chain Management; Supply Chain; Sustainability; Sustainability Supply Chain Management